PENGEMBANGAN PERMAINAN KARTU TRUTH OR DARE UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA SMP/MTs - Agum Ginanjar; Ecep Supriatna; Dona Fitri Annisa (IKIP Siliwangi, 2023)
This research is motivated by the low self-confidence that occurs in SMP/MTs students. Whereas a self-confidence is a very important part and becomes the main capital for students in maximizing their potential during learning activities. The method used adapts the concept of R&D (Research and Development) Borg and Gall (1983). the stages carried out in this study were only up to the validation test. The research subjects were students of class VIII at MTs Ar-Rosyid. The overall results of the study obtained an average of 80.5%, so it can be concluded that the research product on the truth or dare card game media to increase students' self-confidence was in the